Design, Multiperspective Investigations, and Performance Analysis of Multirotor Unmanned Aerial Vehicle for Precision Farming - Darshan Kumar Jayaram; Vijayanandh Raja; Beena Stanislaus Arputharaj; Hussein A. Z. AL-bonsrulah (International Journal of Aerospace Engineering)
Farming and agriculture are the oldest professions, but they are adapting to the technology revolution to accommodate the world’s growing population. UAV technology is part of the agriculture revolution, which aims to boost crop yields, properly monitor fields, and handle manpower shortages and resource efficiency. Rural India’s tiny farmers cannot afford UAV technology; therefore, it has not yet spread. Payload capacity, endurance, and selective spraying are other considerations. Thus, a low-cost, long-lasting UAV is necessary. This study modified the arm assembly to create a cheap hexacopter UAV. The endurance increased by 10% when 1.5 kg was lost. ABS plastic was used to make the modular arm. For working loads of 9 kg and 10 kg, pesticide/fertilizer spraying saves time, money, and manpower. Thus, a pressure-area coverage-cone angle connection is needed. This study examined spray patterns at different pressures and heights by varying flat fan nozzle and complete cone nozzle orifice diameters. These factors were linked, helping farmers choose the right nozzle. This nozzle was installed in the UAV and field-tested for paddy crops, showing a significant production improvement and lower operational cost. Chemical use pollutes and leaves traces in produce. Precision farming with artificial intelligence (AI) has solved this problem. In this experiment, AI algorithms were used to lemon leaves. Three AI systems were tested on different datasets to forecast plant stress by analyzing leaves due to technical constraints. CNN’s accuracy and computing speed make it ideal for precision farming. This work’s UAV was 30% cheaper than commercial UAVs and had more durability. Farmers will also benefit from the flat fan and complete cone nozzles’ pressure-area coverage connection.